Treatment Buddies Improve Clinic Attendance among Women but Not Men on Antiretroviral Therapy in the Nyanza Region of Kenya - Charles Kibaara; Cinthia Blat; Jayne Lewis-Kulzer; Starley Shade; Patrick Mbullo; Craig R. Cohen; Elizabeth A. Bukusi (AIDS Research and Treatment)
Background. Kenyan antiretroviral (ART) guidelines encourage treatment buddies (TBy) to maximize treatment adherence. This study examined the effect of TBys on clinic attendance in men and women on ART. Methods. This retrospective cohort study included all adult patients initiating ART from August 2007 to December 2011 at four health facilities in Kenya. Data were abstracted from electronic medical records and analyzed using Poisson regression. Results. Of 2,430 patients, 2,199 (91%) had a TBy. Relationship between TBy and clinic attendance differed in females and males (interaction p=0.09). After demographic and clinic factor adjustment, females with a TBy were 28% more likely to adhere to all appointments than those without (adjusted aRR = 1.28; 95% CI 1.08–1.53), whereas males were no more likely to adhere (aRR = 1.01; 95% CI 0.76–1.32). Males reported partner/spouse (33%) or brother (11%) as the TBy while females reported sister (17%), partner/spouse (14%), or another family member (12%). Multivariable analysis found no association between clinic attendance and TBy relationship in either gender. Conclusion. Clinic attendance was higher among women with TBys but not men. Results support TBys to help women achieve ART success; alternate strategies to bolster TBy benefits are needed for men.